Gingko biloba extract improves the lipid profile, inflammatory markers, leptin level and the antioxidant status of T2DM patients poorly responding to metformin: A double- blind, randomized, placebo-controlled trial - Saad Abdulrahman Hussain; Tavga Ahmed Aziz; Taha Othman Mahwi; Zheen Aorahman Ahmed (Universidade de São Paulo, 2022)
Abstract The present study aims to evaluate the effects of Ginkgo biloba (GKB) extract as "add- on" therapy with metformin on the lipid profile, inflammatory markers, leptin and the total antioxidant capacity (TAOC) of patients with type 2 diabetes mellitus (T2DM). It is a multi- center, randomized, placebo-controlled double-blinded clinical study. Sixty patients were allocated into two groups: control and treatment groups; they received orally either 120 mg starch/capsule or 120mg GKB/capsule, respectively as an adjuvant with metformin for 90 days. Blood samples were obtained at zero time and after 90 days. The blood was utilized for analysis of the lipid profile, inflammatory markers, leptin, and TAOC. The GKB extract produced a significant decrease in the levels of TG, LDL-c, and CRP, with a significant increase in HDL-c compared to baseline values. There were no significant changes reported in the placebo-treated group. It also produced a significant decrease in the concentrations of IL-6, TNF-α, and leptin compared to baseline values and placebo-treated groups with a significant increase in TAOC compared to baseline values. In conclusion, GKB extract, as an adjuvant with metformin, decreases inflammatory mediators, leptin level and improves the antioxidant status and lipid profile of T2DM patients improperly managed with metformin.